Early and late effects of absorbable poly(vinyl alcohol) hernia mesh to tissue reconstruction - Daniella Fehér; Andrea Ferencz; Györgyi Szabó; Krisztina Juhos; Domokos Csukás; Constantinos Voniatis; Lilla Reininger; Kristóf Molnár; Angéla Jedlovszky‐Hajdú; György Wéber (IET Nanobiotechnology)
Abstract Hernia is a defect of the abdominal wall. Treatment is principally surgical mesh implantation. Non‐degradable surgical meshes produce numerous complications and side‐effects such as inflammatory response, mesh migration and chronic pain. In contrast, the biodegradable, poly (vinyl alcohol) (PVA) based polymers have excellent chemical, mechanical and biological properties and after their degradation no chronic pain can be expected. The toxicology of PVA solution and fibers was investigated with Human dermal fibroblast‐ Adult cell line. Implantation tests were observed on long‐term contact (rat) and large animal (swine) models. To measure the adhesion formation, Diamond and Vandendael score were used. Macroscopical and histological responses were graded from the samples. In vitro examination showed that PVA solution and fibers are biocompatible for the cells. According to the implantation tests, all samples were integrated into the surrounding tissue, and there was no foreign body reaction. The average number of adhesions was found on the non‐absorbable suture line. The biocompatibility of the PVA nanofiber mesh was demonstrated. It has a non‐adhesive, non‐toxic and good quality structure which has the potential to be an alternative solution for the part of the hernia mesh.